2012
DOI: 10.1037/a0026118
|View full text |Cite
|
Sign up to set email alerts
|

Contemplative/emotion training reduces negative emotional behavior and promotes prosocial responses.

Abstract: Contemplative practices are believed to alleviate psychological problems, cultivate prosocial behavior and promote self-awareness. In addition, psychological science has developed tools and models for understanding the mind and promoting well-being. Additional effort is needed to combine frameworks and techniques from these traditions to improve emotional experience and socioemotional behavior. An 8-week intensive (42 hr) meditation/emotion regulation training intervention was designed by experts in contemplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
0
14

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(194 citation statements)
references
References 56 publications
12
164
0
14
Order By: Relevance
“…Indeed, previous research has found reliable associations between individual differences in RT latencies in an LDT and actual behaviour (e.g. Campos-Melady & Smith, 2012;Kemeny et al, 2012). Further research could extend the current work by examining whether and how the differences in RT latencies found in the present study translate into behaviour.…”
Section: Data For Non-words and Incorrect Responses Were Excluded Rtsupporting
confidence: 57%
“…Indeed, previous research has found reliable associations between individual differences in RT latencies in an LDT and actual behaviour (e.g. Campos-Melady & Smith, 2012;Kemeny et al, 2012). Further research could extend the current work by examining whether and how the differences in RT latencies found in the present study translate into behaviour.…”
Section: Data For Non-words and Incorrect Responses Were Excluded Rtsupporting
confidence: 57%
“…The program was designed by experts in contemplative traditions and emotional science, and aimed at reducing Bdestructive enactment of emotions^and enhancing prosocial responses. Results of a first study about this program suggested that increased awareness of mental processes can influence emotional behavior, and supported the benefit of integrating contemplative theories/practices with psychological methods of emotional regulation (Kemeny et al 2012).…”
Section: Retreat Trainingmentioning
confidence: 76%
“…Classes were theoretical and practical. Training was centered upon emotion, emotional characteristics, emotional recognition in oneself and others, emotional balance (Ekman 2003), and secularized forms of Shamatha, Four Immeasurables, and Vipassana, in order to help participants achieve relaxation, stillness, clarity, and a better emotional balance (Kemeny et al 2012). During breaks and free time, trainees were recommended to keep their routine with as little stimulus and as much silence as possible, avoiding, for example, Internet or computer use to maintain their mind relaxed, stable, and vivid.…”
Section: Retreat Trainingmentioning
confidence: 99%
“…Tested on a sample of 82 female teachers (preK-12) utilizing a randomized, controlled trial design, the training signifi cantly reduced self-reported depressive symptoms and rumination and increased emotional self-awareness (Kemeny et al, 2012 ). Female teachers were chosen for the study because measures of cortisol reactivity were included and there can be differential effects by sex.…”
Section: Mindfulness-based Approaches To Promoting Teachers' Well-beimentioning
confidence: 99%